Sosialiasi Dan Edukasi Preventif Covid-19 Pada Pedagang Di Desa Kedunganyar Kecamatan Wringinanom Kabupaten Gresik - Noerchoidah Noerchoidah; Ch. Menuk Sri H; Nurdina; Ayuni Afri Dani Putri (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
The Covid-19 pandemic has spread widely to various countries and regions, including East Java. The number of deaths due to covid-19 continues to grow. Traders are vulnerable to covid-19 transmission because they have many contacts with buyers who come from various places such as traders who sell in the village of Kedunganyar-Wringinanom-Gresik. Traders' knowledge about covid-19 and efforts to decide on the spread of it still needs to be improved. Activities that can be carried out to increase knowledge about Covid-19 through socialization and education. Socialization and education are carried out by providing information and ways to overcome the spread of Covid-19 as a preventive measure. The increase in traders' knowledge is observed when the traders carry out trading activities. The results obtained by traders are increasingly realizing the importance of washing hands and using masks to break the chain of spreading the covid-19 virus. During the implementation of socialization and education activities, the traders responded positively and were supported by the Covid-19 task force and local village government officials.